Participation in and gains from traditional vegetable value chains: A gendered analysis of perceptions of labour, income and expenditure in producers’ and traders’ households - Fischer, Gundula; Patt, Nicolas; Ochieng, Justus; Mvungi, Henry (Springer, 2020)
Horticulture is one of the fastest growing subsectors of agriculture in Tanzania. Gender relations in vegetable-producing and vegetable-trading households need to be understood to make value chain development equitable. This study, carried out in northern and central Tanzania, is based on data from surveys, focus group discussions and semi-structured interviews. The perceptions of men and women traders and producers are investigated with regard to labour participation in traditional vegetable value chains and gains (income and expenditure) from it. Farmers were found to report more balanced intra-household labour arrangements paired with less-balanced income and expenditure shares, while traders indicated less-balanced labour contributions that went hand in hand with more-balanced shares of benefits. Farmers related limited household development not only to imbalances in benefits but also to a lack of trust and cooperation between spouses. The importance of gender-transformative approaches in agricultural value chains is emphasized herein.